2016
DOI: 10.1142/s1758825116500733
|View full text |Cite
|
Sign up to set email alerts
|

An Arnoldi-Frontal Approach for the Stability Analysis of Flows in a Collapsible Channel

Abstract: In this paper, we have developed a new approach based on a combination of the Arnoldi and frontal methods, which is suitable for solving large sparse asymmetric and generalized complex eigenvalue problems. The new eigensolver seeks the most unstable eigen-solution in the Krylov subspace and makes use of the efficiency of the frontal solver developed for the finite element methods. The approach is used for a stability analysis of flows in a collapsible channel and is found to significantly improve the computati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 48 publications
2
6
0
Order By: Relevance
“…These points agree well with the neutral stability curve of Hao et al. (2016), and the slight differences are attributed to the difference between the two constitutive laws (the critical Reynolds number is displaced by less than 1 % for all points tested). In general, the lower static branch becomes unstable as the Reynolds number increases (similar to Heil 2004; Stewart 2017; Herrada et al.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…These points agree well with the neutral stability curve of Hao et al. (2016), and the slight differences are attributed to the difference between the two constitutive laws (the critical Reynolds number is displaced by less than 1 % for all points tested). In general, the lower static branch becomes unstable as the Reynolds number increases (similar to Heil 2004; Stewart 2017; Herrada et al.…”
Section: Resultssupporting
confidence: 90%
“…(2008) (see also Hao et al. 2016) showed that this neutral stability curve is non-monotonic and for large the system restabilises again as the Reynolds number becomes sufficiently large, although we did not investigate this regime.
Figure 5.An overview of the parameter space spanned by the Reynolds number and extensional stiffness, summarising the steady and unsteady solutions of the model.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations